From Little London to Little Bengal: religion, print, and modernity in early British India, 1793-1835 - White, Daniel E. (The Johns Hopkins University Press, 2013)
The British Empire in India involved recursive transactions between the global East and West, channeling cultural, political, and religious formations that were simultaneously distinct and shared, local, national, and transnational.